Efisiensi Teknis dan Total Faktor Produktivitas Sektor Pertanian di Jawa Tahun 2020 - Nurhanifa, Ira; Budiasih, Budiasih (Seminar Nasional Official Statistics, 2023)
Agriculture is an important sector in the Indonesian economy. Based on data from Statistics Indonesia, the contribution of the agricultural sector to Gross Domestic Product (GDP) always ranks third largest after the manufacturing sector and the wholesale and retail trade sector. However, the contribution and growth of the agricultural sector GDP continues to decline from year to year. This indicates a slowdown in the performance of the agricultural sector compared to other sectors. This study aims to analyze the productivity of the agricultural sector as measured by the value of Total Factor Productivity (TFP) and to determine whether there exist inefficiency in the production process of the agricultural sector and its determinants in Java. The method used is Stochastic Frontier Analysis. The results showed that the productivity of the agricultural sector in Java was relatively low with an average TFP of 0,8150. Then it was found that there is a technical inefficiency problem in the agricultural production process in Java with an average of 0,2498. This means that the agricultural sector in Java in 2020 has not been able to reach its maximum production level due to the production process that is not fully efficient. Manufacturing sector GRDP, population growth, and government expenditure on agriculture have a negative and significant effect on agricultural technical inefficiency.